2018
DOI: 10.3892/ijmm.2018.3455
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of adenovirus-mediated erythropoietin expression on the spiral ganglion neurons in the rat inner ear

Abstract: The aim of the present study was to evaluate the expression of erythropoietin (Epo) and the Epo receptor (Epo-R) in the spiral ganglion neurons (SGNs) of the rat inner ear, and to assess the effect of Epo adenovirus vector (Ad-Epo) on the spontaneous apoptosis of SGNs. A total of 60 ears from 30 healthy neonatal (2-3 days postnatal) Sprague-Dawley rats were used to examine the expression of Epo in the SGNs. The rats were divided into three groups: The negative control group, the vector control group [infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Although previous reports place erythropoietin (EPO) as an ototoxic agent, by inducing vasoconstriction [69], various animal models showed that it protects the inner ear from ototoxic damage, observed through cell cultures and ABR. Thus, expression of Epo and Epo-R was detected by immunohistochemistry and dual immunofluorescence staining using polyclonal antibodies directed against Epo and Epo-R, followed by confocal laser scanning microscopy following Epo adenovirus vector infection [70]. In Epo-transgenic mice, lesser ABR threshold shifts after aminoglycoside-induced hearing loss were found, compared with the control group [71].…”
Section: Erythropoietinmentioning
confidence: 99%
“…Although previous reports place erythropoietin (EPO) as an ototoxic agent, by inducing vasoconstriction [69], various animal models showed that it protects the inner ear from ototoxic damage, observed through cell cultures and ABR. Thus, expression of Epo and Epo-R was detected by immunohistochemistry and dual immunofluorescence staining using polyclonal antibodies directed against Epo and Epo-R, followed by confocal laser scanning microscopy following Epo adenovirus vector infection [70]. In Epo-transgenic mice, lesser ABR threshold shifts after aminoglycoside-induced hearing loss were found, compared with the control group [71].…”
Section: Erythropoietinmentioning
confidence: 99%
“…For SGN therapy, the effects of EPO treatment are highly varied. There are reports that EPO treatment (i) decreases spontaneous apoptosis of cultured murine SGN ( Zhong et al, 2018 ), (ii) results in significantly less SGN loss in an animal model of SNHL ( Bächinger et al, 2018 ), (iii) has no positive effect on SGN survival but promotes neurite outgrowth ( Berkingali et al, 2008 ) or (iv) has no effect on survival or neurite outgrowth after administration ( Kaiser et al, 2013 ). Additionally, in clinical trials on neurodegenerative disease, EPO often fails to be protective as recently reviewed by Vittori et al (2021) .…”
Section: Introductionmentioning
confidence: 99%